"Unitarianism, Universalism, and Unitarian Universalism" - McKanan, Daniel (2013)
Unitarian Universalism is a liberal religious tradition with denominational roots in the late eighteenth and early nineteenth centuries, and theological roots stretching back to the Radical Reformation and the patristic period. Originally two traditions of liberal Christianity, its current non-creedal form includes Christian, Buddhist, Jewish, pagan, mystical, process, and humanist spiritualities.